Relative recency influences object-in-context memory - Tam, Shu K.E.; Bonardi, Charlotte; Robinson, Jasper (Elsevier, 2015)
In two experiments rats received training on an object-in-context (OIC) task, in which they received preexposure to object A in context x, followed by exposure to object B in context y. In a subsequent test both A and B are presented in either context x or context y. Usually more exploration is seen of the object that has not previously been paired with the test context, an effect attributed to the ability to remember where an object was encountered. However, in the typical version of this task, object A has also been encountered less recently than object B at test. This is precisely the arrangement in tests of ‘relatively recency’ (RR), in which more remotely presented objects are explored more than objects experienced more recently. RR could contaminate performance on the OIC task, by enhancing the OIC effect when animals are tested in context y, and masking it when the test is in context x. This possibility was examined in two experiments, and evidence for superior performance in context y was obtained. The implications of this for theoretical interpretations of recognition memory and the procedures used to explore it are discussed.